IDENTIFICATIONS CONCEPTUELLES DE L’INTERACTION „POLITIQUE ÉTRANGÈRE – INTÉRÊT NATIONAL – PROCESSUS INTÉGRATIONNISTE” - Cebotari, Svetlana; Cotilevici, Violeta (My University, 2018)
In the contemporary world, the integration is one of the primary factors of the foreign policy and of the international relations as a whole. At the beginning of the 21st century the world is going through a multitude of processes that take place inside and outside the states. New integrationist groups appear, the organizational forms are diversified and the evolution takes place from simplistic models to more complex ones. As a result, the integrationist processes en-compassed virtually all regions and states, thus contributing to the formation of new international "matrices". This article analyzes the relationship «national interest - foreign policy - integrationist process". Between the notions of "integrationist process" and "national interest", "foreign policy" there is a complementarity report, each one completing one ano-ther. No integration process can be achieved outside and without the involvement of the states, which have a certain interest, which they achieve through the foreign policy.
Conceptual identifications of the «foreign policy – national interest – process of integration» interaction
Keywords: interest; integrationist process; national interest; foreign policy; international relations